The offshore wind speed changes in China: an insight into CMIP6 model simulation and future projections - Kaiqiang Deng; Song Yang; Wanlei Liu; Hairong Li; Deliang Chen; Tao Lian; Gangfeng Zhang; Jinlin Zha; Cheng Shen (Climate Dynamics, 2024)
Offshore wind speed in China plays a key role in affecting air–sea interactions, coastal tides, and wind energy, but its changes in a warming climate and the associated causes remain unclear. Based on the ERA5 reanalysis and the Coupled Model Intercomparison Project Phase 6 (CMIP6) models, this study evaluates the past and future variations of wind speed at 10 m (WS10) over China’s offshore seas in summer and winter. The results show that the CMIP6 multi-model mean performs well in simulating the climatological patterns (1981–2010) of WS10 for both seasons. The trends and leading variabilities in WS10 are also reasonably reproduced in the South China Sea (SCS). In the northern SCS, WS10 has strengthened during both seasons in the recent decades. In contrast, in the East China Sea (ECS), WS10 has increased (decreased) during summer (winter). Further attribution analysis suggests that the forcing of greenhouse gasses (aerosols) may make WS10 stronger (weaker) in the two seas and for both seasons, while natural variability tends to slow down (speed up) WS10 in the SCS and ECS during summer (winter). In addition, according to the CMIP6 model projections under various warming scenarios, WS10 is likely to increase over both the northern SCS and the ECS in summer, while WS10 will increase over the northern SCS but decrease over the ECS in winter. Differences in the projected WS10 changes in the ECS during summer and winter are attributed to the projected intensification (weakening) of the East Asian summer (winter) monsoon circulation.